2015
DOI: 10.1002/mus.24593
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic stress relaxation in the hamstrings before and after a 10‐week stretching program

Abstract: Individuals who participated in a 10-week hamstrings passive-static stretch program had a reduced RSR response. A higher stretch intensity or longer duration may be necessary to achieve RSRs similar to those reported before the stretch program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Flexibility training was the most preferred exercise type, followed by resistance and endurance training. Benefits of flexibility exercise include the promotion of well-being and relaxation [ 17 ]. Therefore, its choice could be an attempt to minimize the psychological impact caused by public life restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…Flexibility training was the most preferred exercise type, followed by resistance and endurance training. Benefits of flexibility exercise include the promotion of well-being and relaxation [ 17 ]. Therefore, its choice could be an attempt to minimize the psychological impact caused by public life restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…Since there is no rigid randomized clinical trial to confirm this suggestion, its reasonableness remains unclear. However, a recent study found that higher stretch intensity or duration might be necessary to achieve better outcomes based on the creep and stress relaxation properties of the soft tissue [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Each participant was familiarized with and properly positioned on the isokinetic dynamometer termed the Flexmachine that was built in the Biomechanics Laboratory of the Federal University of Minas Gerais (UFMG, Belo Horizonte, Brazil) (for details see Peixoto et al 2015). All equipment settings were recorded for future use (Cabido et al 2014).…”
Section: Methodsmentioning
confidence: 99%
“…In this study we used a repeated-measures design to assess hamstring flexibility via an isokinetic knee extension test as previously described (Cabido et al 2014;Peixoto et al 2015). Participants were seated on the Flexmachine with the distal third of the thigh supported at 45º hip flexion relative to the ground.…”
Section: Experimental Approachmentioning
confidence: 99%